Who Are Atrocity's "Real" Perpetrators, Who Its "True" Victims and Beneficiaries?. Issue 3 (4th September 2014) - Osiel, Mark
<x content-type="archive" xml:space="preserve">Abstract</x> Modern law's response to mass atrocities vacillates equivocally in how it understands the dramatis personae to these expansive tragedies, at once extraordinary and ubiquitous. Is there any principled order to this? If not, should we care?